2011
DOI: 10.1063/1.3530844
|View full text |Cite
|
Sign up to set email alerts
|

Aging effects on the nucleation of Pb nanoparticles in silica

Abstract: The ion beam synthesis of Pb nanoparticles (NPs) in silica is studied in terms of a two step thermal annealing process consisting of a low temperature long time aging treatment followed by a high temperature short time one. The samples are investigated by Rutherford backscattering spectrometry and transmission electron microscopy. The results obtained show that highly stable Pb trapping structures are formed during the aging treatment. These structures only dissociate at high temperatures, inhibiting the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 20 publications
(18 reference statements)
4
44
0
Order By: Relevance
“…The peak positions of Pb (1 1 1) are the same as the ones of Si (1 1 1), indicating a cube-on-cube epitaxial relationship between the Pb NPs and the Si matrix. Therefore, we can conclude that the fcc-Pb NPs are crystallographically oriented with respect to the Si matrix according to Pb Formation of Pb NPs growing in parallel alignment with the Si matrix after implantation and subsequent annealing is in good agreement with earlier observations [20,41,42], where TEM was used to verify the existence of aligned Pb NPs. In addition, the hexagonal shape of the Pb NP perpendicular to the Si [0 1 1] zone axis (figure 7(a)) indicates that the particle shape is a truncated octahedron bounded by {1 1 1} and {0 0 1} planes.…”
Section: Crystallographic Orientation and Lattice Constants Of The Fcsupporting
confidence: 75%
“…The peak positions of Pb (1 1 1) are the same as the ones of Si (1 1 1), indicating a cube-on-cube epitaxial relationship between the Pb NPs and the Si matrix. Therefore, we can conclude that the fcc-Pb NPs are crystallographically oriented with respect to the Si matrix according to Pb Formation of Pb NPs growing in parallel alignment with the Si matrix after implantation and subsequent annealing is in good agreement with earlier observations [20,41,42], where TEM was used to verify the existence of aligned Pb NPs. In addition, the hexagonal shape of the Pb NP perpendicular to the Si [0 1 1] zone axis (figure 7(a)) indicates that the particle shape is a truncated octahedron bounded by {1 1 1} and {0 0 1} planes.…”
Section: Crystallographic Orientation and Lattice Constants Of The Fcsupporting
confidence: 75%
“…Previous studies of Pb implanted SiO 2 have found (before thermal annealing) Pb clusters [9,10] as well as Pb\O interactions [10]. Note that both of these studies used a much higher implantation energy (~300 keV) than the current study (30 keV) which leads to ion depths of~100 nm rather than the~20 nm here.…”
Section: Discussionmentioning
confidence: 62%
“…While one likely would not see such strong spectral weight from Pb\O bonding in the SiO 2 :Pb due to the lower relative concentration of Pb, it provides an indication of the type of feature one would expect to see. Thus, it is evident that in this case the Pb ions interact minimally with the O atoms of the host SiO 2 (either through the formation of oxide clusters or as single substitutional or interstitial atoms), and instead they likely aggregate into metallic clusters, as found in previous studies [9,10]. The gradual onset in the pre-edge of the SiO 2 :Pb XAS spectrum could be due to interactions between the surfaces of the Pb clusters and the O atoms of the SiO 2 , or simply due to damage in the SiO 2 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations